The income structure of smallholder forest farmers in rural Sumbawa, Indonesia - BUDIMAN ACHMAD; DIAN DINIYATI (Society for Indonesian Biodiversity, 2018)
Achmad B, Diniyati D. 2018. The income structure of smallholder forest farmers in rural Sumbawa, Indonesia. Biodiversitas 19: 936-946. This research investigated the economic well-being of forest farmers in Labuhan Badas Village, Sumbawa regency of Indonesia. It aimed: (i) to describe the daily economic activities of community-based forest (HKm) farmers who reside inside the state forest and of farmers in privately owned forest (POF) who reside outside the state forest areas; and (ii) to analyse their income structure in relation to the corresponding economic activities. The research was conducted from August 2015 to April 2016. The survey sample consisted of 34 HKm and 34 POF farmers who were selected purposively. Data collected through interview and focus group discussion techniques were analyzed descriptively. The research determined that the incomes of HKm farmers were generated from14 sources, mainly from activities in the non-agricultural sector, while those for POF farmers were generated from 12 sources mainly from activities in the agricultural sector. The total income of HKm farmers was significantly lower than the income of POF farmers and indicated a moderate level of economic disadvantage. The economic welfare of farmers in both research locations has been assessed to be below an adequate level. Therefore various economic innovations such as the cultivation of honey bees and the processing of unused potential resources (e.g. making wine from cashew fruit) are needed to accelerate the attainment of a decent level of economic well-being